A 2007 social accounting matrix for Guinea Bissau - Cabral, François Joseph (International Food Policy Research Institute, 2015)
In this technical brief, we first present the architecture of the Social Accounting Matrix (SAM) of Guinea Bissau. We then give an overview of the various steps followed during its construction and finally conduct a quantitative analysis of the economy of Guinea Bissau based on a SAM developed for 2007.